Rescinding evidence-based care and practices during the initial COVID-19 outbreak in the United States: a qualitative study of the experiences of lactation support providers - Grady, Julie; Mulpeter, Ellie; Brimdyr, Kajsa; Cadwell, Karin (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic disrupted healthcare systems and services including along the childbearing continuum. The aim of this study was to explore the experiences and perceptions of professional lactation support providers who cared for breastfeeding families during the early months of the pandemic (March 2020 – August 2020) in the United States. Design/methods We conducted a qualitative survey among active lactation support providers in the United States. Eligible participants spoke English, were Certified Lactation Counselors who maintained an active certification and who provided lactation care and services prior to and after the onset of the COVID-19 pandemic. Participants were recruited via email from the national database of Certified Lactation Counselors obtained from the national certification body. All ten Health and Human Service regions of the United States were included. Demographic data was collected on each respondent. Qualitative survey responses were analyzed thematically following the framework method. Findings Six-hundred and seventy-four (674) Certified Lactation Counselors responded to the survey from June to July of 2022. Their responses fell within the overarching theme of rescinding evidence-based care and practices that had been in place prior to the pandemic. Affected care practices included the insertion of limits on access to care and insinuating stigma and bias based on COVID-19 status. Irregular appointment schedules and staffing shortages also affected care. Participants reported that separation of the mother and their infant became the norm. Decisions made by management seemed to be grounded in fear and uncertainty, rather than on the evidence-based principles that had been in place prior to the pandemic. Conclusion A lack of coordination, consistency and support, along with fear of the unknown, troubled lactation support providers and impacted their ability to provide evidence-based care and to maintain access to care for all families. The findings of the survey and analysis underscore the importance of adequately preparing for future public health crises by determining how evidence-based care and practices can be preserved in emergent situations.